Academic Dads Balance from the Sidelines: Waiting to Get in the Game. - Vancour, Michele L. (2009)
Keywords: dept.pch; faculty_collection; sabbatical_report

Assisted reproductive technology: Ethical challenges for business and medicine - Flynn, D. (International Journal of Interdisciplinary Social Sciences, 2009)
Assisted Reproductive Technology (ART) is a modern technological tool that provides otherwise infertile individuals and couples an opportunity to conceive. As a multimillion dollar business, ART faces challenges common to other highly profitable enterprises, such as how and when to measure success. This poses ethical challenges as well, though these are unlike the ethical challenges faced by businesses which trade in consumer goods. ART makes babies. Individuals and couples seeking ART may be both vulnerable and fragile, thus ART providers must gently balance smart business practices with ethical care delivery. Applying Laura Nash's integrated approach to business ethics may offer ART providers a suitable model that combines ethically sound care with economically sound business practice. Key to Nash's approach are value creation, economic and social benefit, and relationship building. Not a short-term approach to quick business decisions, Nash's approach requires a long-term commitment as a way of doing business. © Common Ground, Deborah Flynn, All Rights Reserved.
0 citations (Crossref) [2023-10-31]
Keywords: Assisted Reproductive Technology; Business Ethics; Infertility; Laura Nash; dept.pch

Impact of communication training on physician expression of empathy in patient encounters - Bonvicini, Kathleen A.; Perlin, Michael J.; Bylund, Carma L.; Carroll, Gregory; Rouse, Ruby A.; Goldstein, Michael G. (Patient Education and Counseling, 2009)
Objective: To examine whether an educational intervention that focused on physician communication training influenced physician ernpathic expression during patient interactions. Methods: This study used a quantitative research method to investigate the influence of communication training on physician-expressed empathy using two measures (global and hierarchical) of physician empathic behavior. Results: The differences in global empathy scores in the physician training group from baseline to follow-up improved by 37%, and hierarchical scores of physician empathic expression improved by up to 51% from baseline scores for the same group. Conclusions: The results strongly supported the hypotheses that training made a significant difference in physician empathic expression during patient interactions demonstrated by both outside observer measures of global ratings and hierarchical ratings of physician empathic behavior. Practice implications: These findings have significant implications for program design and development in medical education and professional training with the potential to improve patient outcomes. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
158 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-942-075-685-084 tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Adult; Communication; Education; Medical; Continuing; Educational intervention; Empathy; Female; Humans; Male; Measurement; Medical education; Middle Aged; Patient-Centered Care; Physician training; Physician-Patient Relations; Physician-patient relations; Quantitative; Research; United States; dept.pch